Relationship Between Parents’ Commitment to their Children’s Education and Level of Students’ Discipline in Public Secondary Schools in Naivasha Sub-County, Kenya. - S.K Mwaniki, Goodeve; Ngunjiri, Dr. M.; Kiumi, Prof. J. Kanjogu (International Journal of Scientific Research and Management (IJSRM), 2018)
The purpose of this study was to assess the relationship between parents’ commitment to their children’seducation and level of students’ discipline in public secondary schools in Naivasha sub-county, Kenya.  Thestudy targeted a total of 197 respondents (constituting 28 head teachers and 169 teachers). A total of 195respondents participated in the study (169 teachers and 26 principals) participated giving a response rate of99%. Purposive sampling technique was used to sample head teachers while Krejcie and Morgan’s (1970)table for determining sample size for teachers. Questionnaires were used as instrument for data collection.SPSS was used to analyze the data where both descriptive and inferential statistics were used. The analyzeddata were presented in terms of graphs and tables. The results showed that there was a significant positiverelationship between parents’ commitment to child’s education and students’ discipline (r = .387, p = .000).Therefore, the null hypothesis that there was no significant relationship between parents’ commitment tochild’s education and students’ discipline was rejected at .05 level of confidence. The study thereforeconcluded that parents’ commitment to child’s education influences students’ discipline in secondaryschools in Naivasha sub-county. It was recommended that parents should be more committed to theirchildren’s’ education. This can be achieved through participating in school meetings and materiallysupporting the education of their children